The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/656892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Dps4 fromNostoc punctiformeATCC 29133 is a member of His-type FOC containing Dps protein class that can be broadly found among cyanobacteria

Abstract: 25Dps proteins (DNA-binding proteins from starved cells) have been found to detoxify H 2 O 2 . At 26 their catalytic centers, the ferroxidase center (FOC), Dps proteins utilize Fe 2+ to reduce H 2 O 2 27 and therefore play an essential role in the protection against oxidative stress and maintaining 28 iron homeostasis. Whereas most bacteria accommodate one or two Dps, there are five 29 different Dps proteins in Nostoc punctiforme, a phototrophic and filamentous cyanobacterium. 30 This uncommonly high number… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The ligation of the ferroxidase center in this protein differs markedly from canonical Dps proteins and closely resembles that of bacterial Bfrs discussed above (191). Finally NpDps4 possesses unusually His-rich ligation of iron at the ferroxidase center and utilizes only O2 and not H2O2 as an oxidant for iron (198). Accordingly a role for this protein has been proposed as an O2 scavenger within heterocysts where nitrogenase activity requires that a microoxic (< 10 μM O2) environment be maintained (199).…”
Section: Fe Storage In Cyanobacteriamentioning
confidence: 76%
See 1 more Smart Citation
“…The ligation of the ferroxidase center in this protein differs markedly from canonical Dps proteins and closely resembles that of bacterial Bfrs discussed above (191). Finally NpDps4 possesses unusually His-rich ligation of iron at the ferroxidase center and utilizes only O2 and not H2O2 as an oxidant for iron (198). Accordingly a role for this protein has been proposed as an O2 scavenger within heterocysts where nitrogenase activity requires that a microoxic (< 10 μM O2) environment be maintained (199).…”
Section: Fe Storage In Cyanobacteriamentioning
confidence: 76%
“…Accordingly a role for this protein has been proposed as an O2 scavenger within heterocysts where nitrogenase activity requires that a microoxic (< 10 μM O2) environment be maintained (199). Based on sequence comparisons to other Dps proteins, it has been suggested that this type of reaction center, which is common amongst, but restricted to, the cyanobacteria (198) be classified as the His-type ferroxidase center.…”
Section: Fe Storage In Cyanobacteriamentioning
confidence: 99%